QUALITY OF SLEEP AND ITS RELATIONSHIP WITH DEPRESSIVE SYMPTOMATOLOGY AND SUICIDALITY IN UNIPOLAR DEPRESSION - ROY, BHASKAR; DAS, PRANAB (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the relationship between sleep quality, depressive symptomatology, and suicidality among patients with unipolar depression. Methods: This hospital-based cross-sectional study was conducted in the Department of Psychiatry, Burdwan Medical College and Hospital, West Bengal. Fifty patients aged 18–60 y, fulfilling ICD-11 criteria for Major Depressive Disorder, were recruited by simple random sampling. Clinical assessment included the Sleep Quality Scale (SQS), Beck Depression Inventory (BDI), and Columbia–Suicide Severity Rating Scale (C-SSRS). Data were analyzed using SPSS version 20.0. Correlations were determined through Pearson’s product-moment and Spearman’s rank-order tests, with p<0.05 considered significant. Results: The majority of participants were aged 30–39 y (44%), and females comprised 62% of the cohort. The mean SQS score was 5.2±1.1, indicating moderate sleep impairment. A strong positive correlation was found between SQS and BDI scores (r = 0.792, p<0.001), signifying that poor sleep quality was associated with greater depressive severity. Moreover, sleep quality correlated significantly with both suicidal ideation (r = 0.61, p = 0.02) and suicidal behavior (r = 0.48, p = 0.01), suggesting that deteriorating sleep quality contributes to increased suicide risk. Conclusion: The study underscores that impaired sleep quality is intrinsically linked with depressive symptom severity and suicidality in unipolar depression. Routine evaluation and management of sleep disturbances may serve as a vital clinical strategy to improve treatment outcomes and reduce suicide vulnerability in this population.